(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discussed the basic models and approaches to the prediction of bankruptcy organizations. There are two basic approaches to the prediction of bankruptcy. The first is based on the financial data and includes handling some coefficients: becoming better known Altmans Z- coefficient (USA), Tafflers coefficient, (UK), and others, as well as the ability to "read a balance sheet." The second comes from datas on bankrupt companies and compares them with the corresponding datas of the study. It is necessary, taking into account international experience in forecasting, for developing a unique mathematical tool specific for economics of Kazakhstan. Also methodology for analyzing financial statements, making it possible to identify the pattern of pre-indicators signal the possible financial insolvency of the enterprise in the foreseeable future.